Innovative resource recovery from industrial sites: a critical review - Huntington, Victoria E.; Coulon, Frederic; Wagland, Stuart T. (MDPI, 2023)
Global net-zero pledges are instigating a societal shift from a fossil-fuel-based economy to renewables. This change facilitates the use of batteries, solar photovoltaic (PV), wind turbines, etc., all of which are underpinned by critical metals. Raw metal extraction is not renewable and environmental pledges made by the government will not be met if this continues. Historic industrial sites contain vast waste stocks. These sites already have an established infrastructure for resource extraction. Applying green solvents and deep eutectic solvents (DES) to such sites for resource recovery alleviates pressure on existing raw extraction processes whilst generating more immediate stores of critical metal along with relatively insignificant environmental impacts. Existing remediation/recovery options have varying metal recovery efficiencies usually combined with high operating costs. Using novel green solvents, such as DES, on historic sites provides an opportunity to recover metals from waste that ordinarily would be looked over. Increased extraction of critical metals from waste material within the UK will reduce reliance on imported metals and improve critical metals security of supply to UK markets and the wider economy The use of these solvents provides an environmentally friendly alternative but also regenerates the legacy of waste from historic industrial sites and consequently implements a circular economy. Adopting the use of green solvents will meet EU environmental pledges, and boost the economy, by recovering metals from legacy sites to meet exponentially growing metal demand.
Keywords: resource recovery; critical metals; green solvents; renewable energy